"Ubicación optima de generación distribuida en redes de distribución" - Rodríguez Salazar, Joffre Raúl (2020)
Distributed generation is presented as a solution to the increase in energy consumption, characterized by being small and medium-power units connected to the distribution system at the points closest to the loads For this, the optimal points at which it can be connected and the maximum generation capacity that the distribution network can support without affecting the normal operation of the system must be considered. The following study presents an algorithm that reduces the losses of the distribution and minimizes energy purchase costs, through the optimal location of distributed photovoltaic generation systems. Consequently, a bibliographic study is carried out based on the optimization problem solving methods aimed at the optimal location of distributed generation units, thereby identifying the variables and operating restrictions that must be met to connect the systems photovoltaic to the distribution network The results obtained that the objectives used in the optimization model indicated the benefit obtained in the reduction of losses and reduction of the economic value in the purchase of energy, identifying its advantages and disadvantages, the results provided by AMPL are corroborated in the software OpenDSS, designed for the analysis of distribution networks with distributed generation units. The space required for photovoltaic units is directly proportional to the nominal power of the installation, while the maximum nominal power of the installation is regulated under the standards established by the Ecuadorian energy regulation and control agency, the use of these studies can contribute to development of intelligent systems that work with distributed generation units, both these standards and non-standards, identifying a means by which the best benefits can be obtained from the installation of these systems. Keywords: Distributed generation, OpenDSS, AMPL, system losses.